2009
DOI: 10.1002/ijc.24591
|View full text |Cite
|
Sign up to set email alerts
|

Eradication of Helicobacter pylori prevents cancer development in subjects with mild gastric atrophy identified by serum pepsinogen levels

Abstract: A longitudinal cohort study was conducted in Helicobactor pyloriinfected middle-aged Japanese males to evaluate the preventive effects of H. pylori eradication on the development of gastric cancer according to the extent of chronic atrophic gastritis (CAG). The extent of CAG was monitored by baseline serum pepsinogen (PG) levels. We followed 3,656 subjects with persistent H. pylori infection and 473 subjects with successful H. pylori eradication for cancer development for a mean (SD) of 9.3 (0.7) years. Groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

14
117
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(133 citation statements)
references
References 56 publications
14
117
0
1
Order By: Relevance
“…Several studies have reported annual incidences of MGC after H. pylori eradication, ranging from 0.1 to 0.5 % in healthy individuals or peptic ulcer patients [26][27][28][29][30][31][32][33], and from 0.8 to 4.1 % in patients after endoscopic resection for early gastric cancer [9,[11][12][13][14][15]. Individuals after endoscopic resection had a higher risk of MGC compared with those who were healthy or had peptic ulcers.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported annual incidences of MGC after H. pylori eradication, ranging from 0.1 to 0.5 % in healthy individuals or peptic ulcer patients [26][27][28][29][30][31][32][33], and from 0.8 to 4.1 % in patients after endoscopic resection for early gastric cancer [9,[11][12][13][14][15]. Individuals after endoscopic resection had a higher risk of MGC compared with those who were healthy or had peptic ulcers.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several reports that showed the incidence and characteristic features of gastric cancer after H. pylori eradication (Take et al 2005;Kamada et al 2005;Takenaka et al 2007;Fukase et al 2008;Ogura et al 2008;Yanaoka et al 2009;de Vries et al 2009). However, many of these included cases whose cancer lesions developed relatively soon after eradication, namely within 2 years after the treatment (Take et al 2005;Kamada et al 2005;Takenaka et al 2007;Fukase et al 2008;Ogura et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies consistently reported that H. pylori eradication had some inhibitory effects on the subsequent development of gastric cancer, at least in certain conditions (Take et al 2005;Takenaka et al 2007;Fukase et al 2008;Ogura et al 2008). However, it also has been revealed that there are sporadic cases of gastric cancer even after successful eradication (Kamada et al 2005;Yanaoka et al 2009;de Vries et al 2009). Hence, careful follow-up with endoscopic examination for possible gastric cancer is necessary even after successful eradication of H. pylori (Kamada et al 2005;de Vries et al 2009;Yanaoka et al 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Including the reports by Yamamoto et al [1] and Matsuo et al [2], [10 studies of GC detected after Hp eradication have been published to date [3][4][5][6][7][8][9][10]. The characteristics of post-eradication GC include: (a) detection *40 months after eradication; (b) lesions are histologically well differentiated; (c) gross lesion morphology is depressed; and (d) the lesions are small (10-20 mm diameter).…”
mentioning
confidence: 99%